The Development of ARI Cases in Work Area X Located in the PT.BKA Motui Area, Kolaka Regency 2019-2021 - Asterina, Devi Cessaria; Rahmawati, Rahmawati; Harun, Aziz; Riana, Muslan; Harmin, Harmin (Waluya The International Science of Health Journal, 2022)
Introduction: Acute Respiratory Infection (ARI) is a respiratory infection that can last for 14 days. Motui Village is one of the villages that has become a mining area. Based on field data, one of the impacts caused by mining activities is an increase in dust blown by the wind into densely populated villages which can cause ARI. This study aims to see the development of ARI cases in residential areas near mining areas. Method: The design of this research is secondary data analysis by looking at data from the Health Center in Motui village which is a mining area. Looking at the development of ARI cases in 2019, 2020, and 2021. The purpose of this research is to see the development of ARI cases in mining areas Result: ARI is in the top 10 diseases in North Konawe Regency. In 2019 incidence of ARI was 111, in 2020 incidence of ARI was 81, and in 2021 incidence of ARI was 120. In the last 3 years, of 10 villages, Motui village was the village with the highest incidence of ARI. Conclusion: The incidence of ARI fluctuate every year for the last 3 years. The number of ARI occurrences in mining areas is higher than in non-mining areas.